Honorary Professor - Zaphiris, Panayiotis (My University, 2026)
Appointment as Honorary Professor in the School of IT at the Nelson Mandela University "in light of your considerable expertise and leadership in the broad area of Inclusive Design and Social Aspects of Computing". The appointment is effective from 1 October 2020 to 31 December 2023, after which it may be renewed.
Keywords: Sciences